Comparative investigations of the spontaneous and stimulated emissions from nitrogen molecules in air with femtosecond laser excitation pulses. (8th March 2016) - Li, Ziting; Chu, Wei; Zeng, Bin; Yao, Jinping; Li, Guihua; Xie, Hongqiang; Wang, Zhanshan; Cheng, Ya
Abstract: We report on experimental investigations on the spontaneous and stimulated emissions from excited nitrogen molecules generated in both linearly and circularly polarized intense laser fields. The spontaneous emission is measured from the side direction of the laser-induced filament whereas the stimulated emission generated by seed amplification is measured in the forward direction of the laser propagation. The comparison between the signal intensities of the spontaneous fluorescence emission and the seed-amplified stimulated emission provides an insight into the population inversion generated in nitrogen molecules with circularly polarized femtosecond laser pulses.